2007
DOI: 10.1111/j.1600-079x.2007.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular signaling pathways involved in cell growth inhibition of human umbilical vein endothelial cells by melatonin

Abstract: Melatonin, an indolamine mainly produced in the pineal gland, has received a great deal of attention in the last decade because of its oncostatic effects, which are due to its immunomodulatory, antiproliferative, antioxidant and its possible antiangiogenesis properties. Herein, we document its antiproliferative action on human umbilical vein endothelial cells (HUVECs). Moreover, the possible cell signaling pathways when melatonin inhibited HUVEC proliferation were explored in this study. Primary HUVECs were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 42 publications
8
69
1
1
Order By: Relevance
“…We found that in MT1/MT2 CGC, melatonin inhibited ERK and Akt kinases. This is similar to the recently reported action of melatonin on ERK and Act in nonneuronal cells that express both MT1 and MT2 receptors (Cui et al, 2008). On the other hand, previous work has shown that in cells which express only MT1 receptors, melatonin stimulates ERK (Bordt et al, 2001;Chan et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that in MT1/MT2 CGC, melatonin inhibited ERK and Akt kinases. This is similar to the recently reported action of melatonin on ERK and Act in nonneuronal cells that express both MT1 and MT2 receptors (Cui et al, 2008). On the other hand, previous work has shown that in cells which express only MT1 receptors, melatonin stimulates ERK (Bordt et al, 2001;Chan et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…In these latter conditions, melatonin also inhibited the phosphorylation (i.e., activity) of serine/threonine kinase Akt (also known as protein kinase B) (Cui et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…MAPK and Akt signaling pathways play a critical role in melatonin-induced antiproliferative events in other cells [4][5][6][7][8][9][10][11][12]. To determine whether MAPK and Akt signaling pathways are involved in the antiproliferative action of melatonin in MG-63 cells, the expression of MAPK components and Akt was evaluated using the western blot method.…”
Section: Melatonin Significantly Inhibited Phosphorylation Of Erk1/2 mentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK) and Akt signaling pathways are responsible for melatonin's antiproliferative actions in some cells, including human umbilical vein endothelial cells [4], human fibroblast-like synoviocyte [5], hepatocarcinoma HepG2 cells [6], human melanoma SK-MEL-1 cells [7], rat glioma cells [8,9], human breast adenocarcinoma MCF-7 cells [10,11], and human osteoblasts [12]. The MAPK family mainly consists of extracellular signal-regulated kinase (ERK1/2), p38, and c-Jun N-terminal kinase (JNK).…”
Section: Introductionmentioning
confidence: 99%